Overindebtedness, unemployment, and poor mental health – and the role of sense of control: a population-based Swiss study - Hämmig, Oliver (Frontiers in Public Health, 2024)
Background: Both overindebtedness and unemployment are critical life events that can result from or lead to poor mental health. What is less known is that the two partly interrelated events frequently go along with a feeling of loss or lack of control in life, which could be the main reason why they are associated with poor mental health. This has not been examined in previous research, particularly not in this combination.: This study used and merged two cross-sectional data sets. Data collected in 2019 on 219 overindebted clients of the four official debt advisory centers in the Canton of Zurich were linked with a comparable subsample of 1,997 respondents from the Swiss Health Survey of 2017. The entire study population covered 2,216 adult individuals living in the Canton of Zurich.Results: Prevalence of no or low sense of control, medium to high psychological distress, and moderate to major depression were much higher among the 44 solely unemployed (36/30/12%), the 189 solely overindebted (73/83/53%), and particularly among the 30 unemployed and overindebted (93/97/60%) than among all 1,953 other survey participants (21/13/7%). Unemployment, overindebtedness, and a (resulting) lack or loss of control were all found to be strong risk factors for the two mental health outcomes under study.Associations or rather negative health effects were partly but not fully mediated by sense of control. Overindebtedness much more strongly predicted psychological distress (ß = -.37) and depression (ß = .17) than unemployment (ß = -.05/.01). Sense of control turned out to be an independent explanatory factor for poor mental health and even the strongest of all (ß = .49/-.59).Conclusions: Improving a person's control beliefs could be a promising measure for preventing mental health disorders in general and in people who are unemployed and overindebted in particular.